A strong rayleigh scattering acoustic fingerprint fiber and a preparation method thereof

CN121165245BActive Publication Date: 2026-10-27WUHAN SHENGXIN OPTOELECTRONIC TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511485233.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-17
Publication Date
2026-10-27
Estimated Expiration
2045-10-17

AI Technical Summary

Technical Problem

传统光纤的这种均匀性特征虽然有利于降低传输损耗,却严重限制了其产生强瑞利散射信号的内在能力

Benefits of technology

[0029](1)本发明提供的强瑞利散射声纹光纤及其制备方法,使用第一组掺杂离子(如钠离子和钾离子)在石英玻璃中沉积实现匹配包层掺杂时,碱金属会造成匹配包层区域玻璃黏度降低,第一组掺杂离子具有高扩散系数,在拉丝过程中从匹配包层中扩散到包层,同时降低包层的玻璃粘度,因此匹配包层和包层的折射率相近;在石英玻璃中使用第二组掺杂离子(如铝离子和钛离子)实现纤芯掺杂时,能够增加纤芯的黏度,并且第二组掺杂离子远小于第一组掺杂剂的扩散系数,大部分第二组掺杂剂在光纤中也保留在纤芯内,有利于增大纤芯和包层之间粘度差异,从而在拉丝过程产生显著的畸变,大大增强瑞利散射信号。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121165245B_ABST
    Figure CN121165245B_ABST
Patent Text Reader

Abstract

The application provides a strong Rayleigh scattering acoustic fingerprint optical fiber and a preparation method thereof, and relates to the technical field of optical fiber processing. The strong Rayleigh scattering acoustic fingerprint optical fiber comprises a cladding, a matching cladding and a core, the matching cladding comprises a first quartz base pipe and a first group of doping ions doped in the first quartz base pipe, the core comprises the first quartz base pipe and a second group of doping ions doped in the first quartz base pipe, and the cladding comprises a second quartz base pipe; the diffusion coefficient of the first group of doping ions is much larger than that of the second group of doping ions; the first group of doping ions comprises sodium ions and potassium ions, and the second group of doping ions comprises aluminum ions and titanium ions. In the application, the first group of doping ions is used to dope the matching cladding, alkali metals can reduce the glass viscosity of the matching cladding and the cladding area, the second group of doping ions is used to dope the core, the viscosity of the core can be increased, the viscosity difference between the core and the cladding is increased, significant distortion is generated in the drawing process, and the Rayleigh scattering signal is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical fiber processing technology, and in particular to a strong Rayleigh scattering acoustic fiber and its preparation method. Background Technology

[0002] In recent years, distributed acoustic sensing (DAS) technology based on phase-sensitive optical time-domain reflectometers (Φ-OTDR) has shown great application potential in fields such as oil and gas resource exploration, perimeter security, infrastructure health monitoring, and seismic wave detection due to its long-distance, high spatial resolution, and real-time monitoring capabilities. The core principle of the DAS system relies on the phase or intensity change of the Rayleigh scattering signal in the detection fiber. The intensity of the Rayleigh scattering signal directly determines the system's signal-to-noise ratio (SNR), detection sensitivity, and positioning accuracy.

[0003] Traditional single-mode silica optical fibers (such as standard G.652.D fiber) are primarily designed to achieve low transmission loss and high bandwidth. Their core (typically germanium-doped silica) and cladding (pure silica or fluorine-doped silica) have very similar viscosity characteristics. This viscosity matching results in minimal viscosity difference between the core and cladding materials during the high-temperature fiber drawing process, making it difficult to generate significant, non-uniform plastic flow or structural distortion. However, it is precisely these submicroscopic density and composition fluctuations (i.e., structural inhomogeneity) that are "frozen" during rapid cooling that are the main source of Rayleigh scattering. While this uniformity characteristic of traditional optical fibers helps reduce transmission loss, it severely limits their inherent ability to generate strong Rayleigh scattering signals. Summary of the Invention

[0004] In view of this, the present invention proposes a strong Rayleigh scattering acoustic fiber and its preparation method. By enhancing the viscosity difference between the core and cladding, significant distortion is generated during the fiber drawing process, which greatly enhances the Rayleigh scattering signal.

[0005] The technical solution of this invention is implemented as follows: On one hand, this invention provides a strong Rayleigh scattering acoustic fiber, comprising a cladding, a matching cladding, and a core. The matching cladding comprises a first quartz substrate and a first group of doped ions doped within the first quartz substrate. The core comprises a first quartz substrate and a second group of doped ions doped within the first quartz substrate. The cladding comprises a second quartz substrate. The diffusion coefficient of the first group of doped ions is much greater than that of the second group of doped ions. The first group of doped ions comprises sodium ions and potassium ions, and the second group of doped ions comprises aluminum ions and titanium ions.

[0006] Based on the above technical solutions, preferably, the average concentration of sodium ions is 0.2~10 ppm and the average concentration of potassium ions is 0.2~10 ppm.

[0007] Based on the above technical solutions, preferably, the average concentration of aluminum ions is 10,000 to 20,000 ppm, and the average concentration of titanium ions is 0.2 to 100 ppm.

[0008] The matching cladding has a refractive index similar to the cladding and a diameter three times that of the core. It contains a first group of dopants selected from Na, K, or their compounds, with an average concentration greater than 0.2 ppm and less than 10 ppm, used to reduce the glass viscosity of the matching cladding, and also contains fluorine. The first group of dopants has a high diffusion coefficient, diffusing from the matching cladding to the cladding during the fiber drawing process, simultaneously reducing the glass viscosity of the cladding. The core contains a second group of dopants selected from Al, Ti, or their compounds, used to increase the viscosity of the quartz glass, and exhibits a 5 × 10⁻⁶ viscosity at temperatures between 2000°C and 2300°C. −13 cm 2 The diffusion coefficient is / s or greater, but much smaller than that of the first group of dopants, so most of the second group of dopants are also retained in the fiber core.

[0009] The matching cladding region contains a first group of dopants selected from Na, K, and their compounds to reduce the viscosity of the matching cladding glass. These first group of dopants, with their large diffusion coefficients, diffuse during the fiber drawing process, thus reducing their concentration to approximately 1 / 10. Therefore, to maintain the average concentration of the first group of dopants in the fiber matching cladding within the range of 0.2–10 ppm, the average concentration of the first group of dopants in the fiber preform should be 20–100 ppm. The core region contains a second group of dopants selected from Al, Ti, or their compounds to increase the viscosity of the quartz glass. The average Al concentration is 10,000–20,000 ppm, increasing the core glass viscosity while simultaneously raising the core's refractive index. The average Ti concentration is 0.2–100 ppm.

[0010] Based on the above technical solutions, preferably, both the first quartz base tube and the second quartz base tube are high-purity silica-based glass doped with fluorine, wherein the atomic concentration of fluorine is 5000~7000 ppm, and the atomic concentration of other impurities in the high-purity silica-based glass is no greater than 10 ppm.

[0011] The matching cladding and the cladding contain fluorine as a dopant to reduce the refractive index, which helps to reduce its viscosity. Therefore, when the matching cladding has a first group of dopant with an average concentration of about 0.2 ppm and fluorine with an atomic concentration of 5000~7000 ppm, Rayleigh scattering can be observed due to the sufficiently reduced viscosity and the large difference in viscosity from the core.

[0012] Based on the above technical solutions, preferably, the diameter of the matching cladding is 2.95 to 3.05 times the diameter of the mold field.

[0013] Mode field diameter (MFD) is the light intensity propagating within an optical fiber, which is 1 / e of its peak value. 2 With a circumferential diameter three times that of the MFD, the MFD can be considered the effective diameter of the fiber core. Since 99.99% of the optical power propagates within a range three times that of the MFD in the fiber, the attenuation of the transmitted light outside this range is negligible. Therefore, the first group of dopants must be diffused to a range three times that of the MFD to enhance Rayleigh scattering within this range.

[0014] On the other hand, the present invention provides a method for preparing the above-mentioned strong Rayleigh scattering acoustic fiber, characterized by comprising the following steps:

[0015] S1. Preparation: After rinsing the surface of the first quartz base tube with high-pressure ultrapure water, install the first quartz base tube on a precision rotary lathe and perform gas path calibration.

[0016] S2. Matching cladding doping: The first set of doped ion precursors, matching cladding precursors and carrier gas oxygen are introduced into the first quartz-based glass tube, and the matching cladding is deposited using chemical vapor deposition.

[0017] S3, Core doping: The second set of doped ion precursors, the core precursors and the carrier gas oxygen are introduced into the first quartz-based glass tube, and the fiber core is deposited by chemical vapor deposition.

[0018] S4. Collapse: The deposited first quartz base tube is melted and collapsed at high temperature into a solid optical fiber preform core.

[0019] S5. Sleeve: The optical fiber preform is formed by cladding a second quartz tube on the outside of the optical fiber preform core rod using the sleeve method, followed by high-temperature melting and shrinking.

[0020] S6. Fiber drawing: The fiber preform is drawn to form a strong Rayleigh scattering acoustic fiber.

[0021] Based on the above technical solutions, preferably, in step S2, the first group of doped ion precursors is a gaseous mixture of potassium chloride and sodium chloride, and the matching cladding precursor is a gaseous mixture of silicon chloride and sulfur hexafluoride.

[0022] Based on the above technical solutions, preferably, in step S3, the solid precursor of the second group of doped ions is a gaseous mixture of aluminum chloride and titanium chloride, and the core layer precursor is silicon chloride gas.

[0023] Based on the above technical solutions, preferably, in steps S2 and S3, during the deposition process, an oxyhydrogen flame torch is used to heat the first quartz base tube from the outside, the temperature of the oxyhydrogen flame is 1800~2000℃, and the first quartz base tube rotates at 50~100 rpm.

[0024] Based on the above technical solutions, preferably, in steps S4 and S5, the high-temperature melting and shrinking is heated by an oxyhydrogen flame torch, and the temperature of the oxyhydrogen flame is 1800~2300℃.

[0025] When the core region of the optical fiber preform contains a second group of dopants, Al 3+ As a glass network structure former, Ti can form a similar structure with SiO2, improving crosslinking degree and viscosity. 4+ This can form a bridging oxygen structure (Ti–O–Si), increasing the polymerization degree of the network structure and enhancing the rigidity and viscosity of the glass. When the viscosity of the glass in the fiber matching cladding region decreases and the viscosity in the fiber core region increases, the Rayleigh scattering signal in the fiber increases significantly. On the other hand, since the second group of dopants does not diffuse into the matching cladding, the viscosity of the matching cladding does not increase. Therefore, a viscosity difference appears at the interface between the fiber core and the cladding, thereby increasing Rayleigh scattering in this area.

[0026] When the diffusion coefficients of each element at a concentration of 100 ppm at the fiber drawing temperature (2300℃) were calculated using molecular dynamics, the diffusion coefficients of Na, K, Al, and Ti are shown in the table below. Based on the results, it can be inferred that Al and Ti will be located within the core diameter range, because the diffusion coefficients of Al and Ti are much smaller than those of Na and K, and the K concentration distribution will diffuse to twice the core diameter during fiber drawing.

[0027]

[0028] The strong Rayleigh scattering acoustic fiber and its fabrication method of the present invention have the following advantages over the prior art:

[0029] (1) The strong Rayleigh scattering acoustic fiber and its preparation method provided by the present invention use a first group of dopant ions (such as sodium ions and potassium ions) to deposit in quartz glass to achieve matching cladding doping. Alkali metals will cause the glass viscosity of the matching cladding region to decrease. The first group of dopant ions has a high diffusion coefficient and diffuses from the matching cladding to the cladding during the fiber drawing process, while reducing the glass viscosity of the cladding. Therefore, the refractive indices of the matching cladding and the cladding are similar. When a second group of dopant ions (such as aluminum ions and titanium ions) is used in quartz glass to achieve fiber core doping, the viscosity of the fiber core can be increased. The diffusion coefficient of the second group of dopant ions is much smaller than that of the first group of dopant ions. Most of the second group of dopant ions are also retained in the fiber core in the fiber, which is beneficial to increase the viscosity difference between the fiber core and the cladding, thereby generating significant distortion during the fiber drawing process and greatly enhancing the Rayleigh scattering signal.

[0030] (2) The strong Rayleigh scattering acoustic fiber provided by this invention has a matching cladding diameter approximately three times the mode field diameter (MFD). MFD is the light intensity propagating within the fiber at its peak value 1 / e 2 With a circumferential diameter approximately three times that of the MFD, the MFD can be considered the effective diameter of the fiber core. Since 99.99% of the optical power propagates within a range three times the MFD in the fiber, the attenuation of the transmitted light outside this range is negligible. Therefore, the matching cladding diameter of this invention is approximately three times the MFD, which is beneficial for enhancing Rayleigh scattering within this range. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0032] Figure 1 This is a schematic diagram of the structure of the strong Rayleigh scattering acoustic fiber of the present invention;

[0033] Figure 2 This is a schematic diagram of the main process flow for the fabrication method of the strong Rayleigh scattering acoustic fiber of the present invention.

[0034] Figure 3 A schematic diagram of the refractive index of the strong Rayleigh scattering acoustic fiber prepared in Example 1 of the present invention;

[0035] Figure 4 This is a potassium concentration distribution diagram along the diameter of the strong Rayleigh scattering acoustic fiber prepared in Example 1 of the present invention.

[0036] Figure 5 This is a diagram showing the aluminum element concentration distribution along the diameter of the strong Rayleigh scattering acoustic fiber prepared in Example 1 of the present invention. Detailed Implementation

[0037] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0038] Example 1

[0039] like Figure 1 As shown, this embodiment provides a strong Rayleigh scattering acoustic fiber, including a cladding 3, a matching cladding 2, and a core 1. The matching cladding includes a first quartz substrate and a first group of doped ions doped within the first quartz substrate. The core includes a first quartz substrate and a second group of doped ions doped within the first quartz substrate. The cladding includes a second quartz substrate. The diffusion coefficient of the first group of doped ions is much greater than that of the second group of doped ions. The first group of doped ions includes sodium ions and potassium ions, and the second group of doped ions includes aluminum ions and titanium ions.

[0040] The average concentration of sodium ions is 0.2 ppm, the average concentration of potassium ions is 0.2 ppm, the average concentration of aluminum ions is 14000 ppm, and the average concentration of titanium ions is 10 ppm.

[0041] The diameter of the matching cladding is three times the diameter of the mode field.

[0042] The first and second quartz tubes are high-purity silica-based glass doped with fluorine, the atomic concentration of fluorine is 6000 ppm, and the atomic concentration of other impurities in the high-purity silica-based glass is no greater than 10 ppm.

[0043] like Figure 2 As shown, this embodiment provides a method for preparing the above-mentioned strong Rayleigh scattering acoustic fiber, including the following steps:

[0044] S1. Preparation: A high-purity quartz base tube is selected as the first quartz base tube. The outer diameter of this quartz glass tube is 35 mm, and the inner diameter is approximately 20 mm. The preparation steps include rinsing the surface with high-pressure ultrapure water to remove adsorbed particles, organic matter, and metallic contaminants. Afterward, the first quartz base tube is installed on a precision rotary lathe for gas path calibration to prevent base tube eccentricity or gas path leakage, which could lead to uneven thickness of the subsequent deposition layer.

[0045] S2. Matching Cladding Doping: Weigh 1.5g of potassium chloride (KCl) and 2.2g of sodium chloride (NaCl) and place them in the matching tube. Heat the materials to 800℃ using an external heat source to generate chloride gas, which is then introduced into the first quartz substrate. Simultaneously, introduce 150 sccm of SiCl4, 9 sccm of SF6, and 1000 sccm of O2, while simultaneously heating the first quartz substrate from the outside with an oxyhydrogen flame torch, moving it back and forth at a speed of 200 mm / min. During the deposition process, the oxyhydrogen flame temperature is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate rotates at 50~100 rpm, moving back and forth with the torch, depositing the first set of dopants on the inner wall of the first quartz substrate. The torch completes ten round trips to complete the deposition, forming the matching cladding, and then allows it to cool naturally.

[0046] S3, Core Doping: Chlorine gas at 15 sccm is introduced into a U-shaped tube containing sufficient aluminum and titanium particles, producing aluminum chloride (AlCl3) and titanium chloride (TiCl3). 4) Gas is introduced into the first quartz substrate. Simultaneously, 200 sccm of SiCl4 and 1000 sccm of O2 are introduced, while the first quartz substrate is heated externally using an oxyhydrogen flame torch, which moves back and forth at a speed of 200 mm / min. During deposition, the oxyhydrogen flame temperature is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate rotates at 50-100 rpm, coordinating with the torch's reciprocating motion to deposit a second set of dopants on the inner wall of the first quartz substrate. The torch completes ten round trips to complete the deposition, forming the core layer, after which it is allowed to cool naturally.

[0047] S4. Collapse: The deposited first quartz substrate is high-temperature shrunk into a solid optical fiber preform core. After the core layer deposition is completed, the deposited first quartz substrate is shrunk into a solid optical fiber preform core using an oxyhydrogen flame. Essentially, this involves inducing viscous flow in the quartz substrate or deposited layer through high temperature. The quartz substrate is heated externally by an oxyhydrogen flame torch, which moves back and forth at a speed of 100 mm / min. During the collapse process, the oxyhydrogen flame temperature is controlled at 2100℃. The quartz substrate rotates at 50~100 rpm, coordinating with the torch's reciprocating movement. The quartz glass enters a viscous flow state, and surface tension dominates the shrinkage deformation. Internal stress is eliminated through axial stretching and rotation. After four rounds of torch movement, a solid optical fiber preform core with a diameter of 18 mm is finally formed.

[0048] S5. Sleeve: The fiber preform is formed by cladding a cleaned second quartz tube on the outside of the fiber preform core using the sleeve method, followed by high-temperature melting and shrinking. After the core and sleeve are assembled, the core and sleeve are melted and fixed at 2100℃ using an oxyhydrogen flame, and then cooled naturally to form the fiber preform.

[0049] S6. Fiber Drawing: The cleaned optical fiber preform is cut to a certain length and vertically fixed at the top of the drawing tower. The drawing furnace is set to a temperature of 1980℃. The tip of the preform melts into a suspended glass droplet, which is stretched by a traction wheel under gravity. The drawing tension is set to 70N, and the drawing speed is 18m / min. A laser diameter gauge monitors the process in real time, controlling the bare fiber diameter to 124.5μm. The bare fiber is rapidly cooled with an inert gas, then coated with a soft inner coating and a hard outer coating, and instantly cured by ultraviolet light. The fiber is then wound onto a take-up reel with tension adjusted to produce the finished optical fiber. The dopant concentration in the fiber after drawing and the Rayleigh scattering at a wavelength of 1550nm are measured.

[0050] Figure 3 The diagram shows the refractive index of the optical fiber prepared in Example 1. As can be seen from the diagram, the cladding has a lower refractive index than the core 1, which is beneficial for enhancing the Rayleigh scattering signal of the optical fiber.

[0051] Figure 4 The figure shows the potassium concentration distribution along the diameter of the strong Rayleigh scattering acoustic fiber prepared in Example 1. As can be seen from the figure, potassium is distributed in the matching cladding and the cladding outside the core layer. The potassium concentration diffuses from the innermost part of the matching cladding outwards, and the concentration gradually decreases. The potassium concentration in the fiber is lower than that in the fiber preform, but the diameter range it covers is wider, about 6.25 times that of the preform. This indicates that after high-temperature drawing, potassium gradually diffuses outwards from the matching cladding along the diameter of the fiber preform.

[0052] Figure 5 The figure shows the aluminum concentration distribution along the diameter of the strong Rayleigh scattering acoustic fiber prepared in Example 1. As can be seen from the figure, the aluminum element is distributed in the core layer. The aluminum element concentration diffuses from the innermost part of the core layer outwards, and the concentration gradually decreases. The aluminum element concentration in the fiber is lower than that in the fiber preform, but the diameter range covered is wider, about 3 times that of the preform. This indicates that after high-temperature drawing, the aluminum element gradually diffuses from the core layer outwards along the diameter of the fiber preform.

[0053] contrast Figure 4 and Figure 5 It is known that the diffusion diameter of potassium is much larger than that of aluminum. This is because at high temperatures, the diffusion coefficient of potassium is greater than that of aluminum, thus allowing it to diffuse further. During the fiber drawing process, potassium diffuses from the matching cladding into the cladding, thereby reducing the glass viscosity of the cladding. In contrast, aluminum remains within the fiber core during the fiber drawing process. This results in the cladding and matching cladding having similar viscosities, but with a significant difference in viscosity from the fiber core. Consequently, the cladding has a lower refractive index than the fiber core, which is beneficial for enhancing the Rayleigh scattering signal of the optical fiber. The optical fiber obtained in Example 1 exhibits an attenuation of 2.23 dB / km at a wavelength of 1550 nm.

[0054] It should be noted that sodium and potassium have the same doping sites and diffusion methods, and titanium and aluminum have the same doping sites and diffusion methods, which will not be elaborated further.

[0055] Example 2

[0056] This embodiment provides a strong Rayleigh scattering acoustic fiber, which is the same as that in Embodiment 1, except that:

[0057] The average concentration of sodium ions is 0.2 ppm, the average concentration of potassium ions is 0.2 ppm, the average concentration of aluminum ions is 10,000 ppm, and the average concentration of titanium ions is 0.2 ppm.

[0058] This embodiment provides a method for preparing the above-mentioned strong Rayleigh scattering acoustic fiber, which is the same as that in Embodiment 1, except that:

[0059] S3. Core Doping: 10 sccm of chlorine gas is introduced into a U-shaped tube containing sufficient aluminum and titanium particles, generating aluminum chloride (AlCl3) and titanium chloride (TiCl4) gases, which are then introduced into the first quartz substrate. Simultaneously, 200 sccm of SiCl4 and 1000 sccm of O2 are introduced, while the first quartz substrate is heated externally using an oxyhydrogen flame torch, which moves back and forth at a speed of 200 mm / min. During the deposition process, the temperature of the oxyhydrogen flame is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate rotates at 50-100 rpm, coordinating with the torch's back and forth movement, to deposit the second set of dopants on the inner wall of the first quartz substrate. The torch completes ten round trips to complete the deposition, forming the core layer, after which it is allowed to cool naturally.

[0060] Example 3

[0061] This embodiment provides a strong Rayleigh scattering acoustic fiber, which is the same as that in Embodiment 1, except that:

[0062] The average concentration of sodium ions is 5 ppm, the average concentration of potassium ions is 5 ppm, the average concentration of aluminum ions is 15000 ppm, and the average concentration of titanium ions is 50 ppm.

[0063] This embodiment provides a method for preparing the above-mentioned strong Rayleigh scattering acoustic fiber, which is the same as that in Embodiment 1, except that:

[0064] S2. Matching Cladding Doping: Weigh 37.5g of potassium chloride (KCl) and 55g of sodium chloride and place them in the matching tube. Heat the materials to 800℃ using an external heat source to generate chloride gas, which is then introduced into the first quartz substrate. Simultaneously, introduce 150 sccm of SiCl4, 9 sccm of SF6, and 1000 sccm of O2, while simultaneously heating the first quartz substrate from the outside with an oxyhydrogen flame torch, which moves back and forth at a speed of 200 mm / min. During the deposition process, the oxyhydrogen flame temperature is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate rotates at 50~100 rpm, and the torch moves back and forth, depositing the first set of dopants on the inner wall of the first quartz substrate. The torch completes ten round trips to complete the deposition, forming the matching cladding, and then allows it to cool naturally.

[0065] S3. Core Doping: Chlorine gas at 20 sccm is introduced into a U-shaped tube containing sufficient aluminum and titanium particles, generating aluminum chloride (AlCl3) and titanium chloride (TiCl4) gases, which are then introduced into the first quartz substrate. Simultaneously, 200 sccm of SiCl4 and 1000 sccm of O2 are introduced, while the first quartz substrate is heated externally using an oxyhydrogen flame torch, which moves back and forth at a speed of 200 mm / min. During deposition, the oxyhydrogen flame temperature is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate rotates at 50-100 rpm, coordinating with the torch's reciprocating motion to deposit the second set of dopants on the inner wall of the first quartz substrate. The torch completes ten round trips to complete the deposition, forming the core layer, after which it is allowed to cool naturally.

[0066] Example 4

[0067] This embodiment provides a strong Rayleigh scattering acoustic fiber, which is the same as that in Embodiment 1, except that:

[0068] The average concentration of sodium ions is 10 ppm, the average concentration of potassium ions is 10 ppm, the average concentration of aluminum ions is 20,000 ppm, and the average concentration of titanium ions is 100 ppm.

[0069] This embodiment provides a method for preparing the above-mentioned strong Rayleigh scattering acoustic fiber, which is the same as that in Embodiment 1, except that:

[0070] S2. Matching Cladding Doping: Weigh 75g of potassium chloride (KCl) and 110g of sodium chloride (NaCl) and place them in the matching tube. Heat the materials to 800℃ using an external heat source to generate chloride gas, which is then introduced into the first quartz substrate. Simultaneously, introduce 150 sccm of SiCl4, 9 sccm of SF6, and 1000 sccm of O2, while simultaneously heating the first quartz substrate from the outside with an oxyhydrogen flame torch, which moves back and forth at a speed of 200 mm / min. During the deposition process, the oxyhydrogen flame temperature is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate rotates at 50~100 rpm, and the torch moves back and forth, depositing the first set of dopants on the inner wall of the first quartz substrate. The torch completes ten round trips to complete the deposition, forming the matching cladding, and then allows it to cool naturally.

[0071] S3. Core Doping: Chlorine gas at 25 sccm is introduced into a U-shaped tube containing sufficient aluminum and titanium particles, generating aluminum chloride (AlCl3) and titanium chloride (TiCl4) gases, which are then introduced into the first quartz substrate. Simultaneously, 200 sccm of SiCl4 and 1000 sccm of O2 are introduced, while the first quartz substrate is heated externally using an oxyhydrogen flame torch, which moves back and forth at a speed of 200 mm / min. During deposition, the oxyhydrogen flame temperature is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate rotates at 50-100 rpm, coordinating with the torch's reciprocating motion to deposit the second set of dopants on the inner wall of the first quartz substrate. The torch completes ten round trips to complete the deposition, forming the core layer, after which it is allowed to cool naturally.

[0072] Comparative Example 1

[0073] This comparative example provides an acoustic fiber, which is the same as that in Example 1, except that:

[0074] The average concentration of sodium ions is 0 ppm, the average concentration of potassium ions is 0 ppm, the average concentration of aluminum ions is 14000 ppm, and the average concentration of titanium ions is 10 ppm.

[0075] This comparative example provides a method for preparing the above-mentioned acoustic fiber, which is the same as that in Example 1, except that:

[0076] S2. Matching Cladding Deposition: 150 sccm of SiCl4, 9 sccm of SF6, and 1000 sccm of O2 are introduced into the first quartz substrate tube. Simultaneously, an oxyhydrogen flame torch is used to heat the first quartz substrate tube externally, moving back and forth at a speed of 200 mm / min. During deposition, the oxyhydrogen flame temperature is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate tube rotates at 50-100 rpm, coordinating with the torch's reciprocating movement. Deposition is completed after ten passes of the torch, forming the matching cladding. The tube then cools naturally.

[0077] S3. Core Doping: 15 sccm of chlorine gas is introduced into a U-shaped tube containing sufficient aluminum and titanium particles, generating aluminum chloride (AlCl3) and titanium chloride (TiCl4) gases, which are then introduced into the first quartz substrate. Simultaneously, 200 sccm of SiCl4 and 1000 sccm of O2 are introduced, while the first quartz substrate is heated externally using an oxyhydrogen flame torch, which moves back and forth at a speed of 200 mm / min. During the deposition process, the temperature of the oxyhydrogen flame is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate rotates at 50-100 rpm, coordinating with the torch's reciprocating movement, to deposit the second set of dopants on the inner wall of the first quartz substrate. The torch completes ten round trips to complete the deposition, forming the core layer, after which it is allowed to cool naturally.

[0078] Comparative Example 2

[0079] This comparative example provides an acoustic fiber, which is the same as that in Example 1, except that:

[0080] The average concentration of sodium ions is 0.2 ppm, the average concentration of potassium ions is 0.2 ppm, the average concentration of aluminum ions is 0 ppm, and the average concentration of titanium ions is 0 ppm.

[0081] This comparative example provides a method for preparing the above-mentioned strong Rayleigh scattering acoustic fiber, which is the same as that in Example 1, except that:

[0082] S2. Matching Cladding Doping: Weigh 1.5g of potassium chloride (KCl) and 2.2g of sodium chloride (NaCl) and place them in the matching tube. Heat the material to 800℃ using an external heat source to generate chloride gas, which is then introduced into the first quartz substrate. Simultaneously, introduce 150 sccm of SiCl4, 9 sccm of SF6, and 1000 sccm of O2, while simultaneously heating the first quartz substrate from the outside with an oxyhydrogen flame torch, which moves back and forth at a speed of 200 mm / min. During the deposition process, the oxyhydrogen flame temperature is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate rotates at 50~100 rpm, and the torch moves back and forth, depositing the first set of dopants on the inner wall of the first quartz substrate. The torch completes ten round trips to complete the deposition, forming the matching cladding, and then allows it to cool naturally.

[0083] S3. Core Deposition: 200 sccm of SiCl4 and 1000 sccm of O2 are introduced into the first quartz substrate tube, while simultaneously heating the first quartz substrate tube externally using an oxyhydrogen flame torch. The torch moves back and forth at a speed of 200 mm / min, and the temperature of the oxyhydrogen flame is controlled at 2000℃ during the deposition process to ensure sufficient gas-phase oxidation. The first quartz substrate tube rotates at 50~100 rpm, coordinating with the torch's back and forth movement. The torch completes ten round trips to complete the deposition, forming the core layer, after which it is allowed to cool naturally.

[0084] Comparative Example 3

[0085] This comparative example provides an acoustic fiber, which is the same as that in Example 1, except that:

[0086] The average concentration of sodium ions is 0 ppm, the average concentration of potassium ions is 0 ppm, the average concentration of aluminum ions is 0 ppm, and the average concentration of titanium ions is 0 ppm.

[0087] This comparative example provides a method for preparing the above-mentioned acoustic fiber, which is the same as that in Example 1, except that:

[0088] S2. Matching Cladding Deposition: 150 sccm of SiCl4, 9 sccm of SF6, and 1000 sccm of O2 are introduced into the first quartz substrate tube. Simultaneously, an oxyhydrogen flame torch is used to heat the first quartz substrate tube externally, moving back and forth at a speed of 200 mm / min. During deposition, the oxyhydrogen flame temperature is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate tube rotates at 50-100 rpm, coordinating with the torch's reciprocating movement. Deposition is completed after ten passes of the torch, forming the matching cladding. The tube then cools naturally.

[0089] S3. Core Deposition: 200 sccm of SiCl4 and 1000 sccm of O2 are introduced into the first quartz substrate tube, while simultaneously heating the first quartz substrate tube externally using an oxyhydrogen flame torch. The torch moves back and forth at a speed of 200 mm / min, and the temperature of the oxyhydrogen flame is controlled at 2000℃ during the deposition process to ensure sufficient gas-phase oxidation. The first quartz substrate tube rotates at 50~100 rpm, coordinating with the torch's back and forth movement. The torch completes ten round trips to complete the deposition, forming the core layer, after which it is allowed to cool naturally.

[0090] Comparative Example 4

[0091] This comparative example provides an acoustic fiber, which is the same as that in Example 1, except that:

[0092] The average concentration of sodium ions is 10 ppm, the average concentration of potassium ions is 10 ppm, the average concentration of aluminum ions is 0 ppm, and the average concentration of titanium ions is 0 ppm.

[0093] This comparative example provides a method for preparing the above-mentioned acoustic fiber, which is the same as that in Example 1, except that:

[0094] S2. Matching Cladding Doping: Weigh 75g of potassium chloride (KCl) and 110g of sodium chloride (NaCl) and place them in the matching tube. Heat the materials to 800℃ using an external heat source to generate chloride gas, which is then introduced into the first quartz substrate. Simultaneously, introduce 150 sccm of SiCl4, 9 sccm of SF6, and 1000 sccm of O2, while simultaneously heating the first quartz substrate from the outside with an oxyhydrogen flame torch, which moves back and forth at a speed of 200 mm / min. During the deposition process, the oxyhydrogen flame temperature is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate rotates at 50~100 rpm, and the torch moves back and forth, depositing the first set of dopants on the inner wall of the first quartz substrate. The torch completes ten round trips to complete the deposition, forming the matching cladding, and then allows it to cool naturally.

[0095] S3. Core Deposition: 200 sccm of SiCl4 and 1000 sccm of O2 are introduced into the first quartz substrate tube, while simultaneously heating the first quartz substrate tube externally using an oxyhydrogen flame torch. The torch moves back and forth at a speed of 200 mm / min, and the temperature of the oxyhydrogen flame is controlled at 2000℃ during the deposition process to ensure sufficient gas-phase oxidation. The first quartz substrate tube rotates at 50~100 rpm, coordinating with the torch's back and forth movement. The torch completes ten round trips to complete the deposition, forming the core layer, after which it is allowed to cool naturally.

[0096] Comparative Example 5

[0097] This comparative example provides an acoustic fiber, which is the same as that in Example 1, except that:

[0098] The average concentration of sodium ions is 0 ppm, the average concentration of potassium ions is 0 ppm, the average concentration of aluminum ions is 20,000 ppm, and the average concentration of titanium ions is 100 ppm.

[0099] This comparative example provides a method for preparing the above-mentioned acoustic fiber, which is the same as that in Example 1, except that:

[0100] S2. Matching Cladding Deposition: 150 sccm of SiCl4, 9 sccm of SF6, and 1000 sccm of O2 are introduced into the first quartz substrate tube. Simultaneously, an oxyhydrogen flame torch is used to heat the first quartz substrate tube externally, moving back and forth at a speed of 200 mm / min. During deposition, the oxyhydrogen flame temperature is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate tube rotates at 50-100 rpm, coordinating with the torch's reciprocating movement. Deposition is completed after ten passes of the torch, forming the matching cladding. The tube then cools naturally.

[0101] S3. Core Doping: Chlorine gas at 25 sccm is introduced into a U-shaped tube containing sufficient aluminum and titanium particles, generating aluminum chloride (AlCl3) and titanium chloride (TiCl4) gases, which are then introduced into the first quartz substrate. Simultaneously, 200 sccm of SiCl4 and 1000 sccm of O2 are introduced, while the first quartz substrate is heated externally using an oxyhydrogen flame torch, which moves back and forth at a speed of 200 mm / min. During deposition, the oxyhydrogen flame temperature is controlled at 2000℃ to ensure sufficient gas-phase oxidation. The first quartz substrate rotates at 50-100 rpm, coordinating with the torch's reciprocating motion to deposit the second set of dopants on the inner wall of the first quartz substrate. The torch completes ten round trips to complete the deposition, forming the core layer, after which it is allowed to cool naturally.

[0102] The concentrations of various dopant ions and Rayleigh scattering attenuation values ​​in the acoustic fiber obtained in Examples 1-4 and Comparative Examples 1-5 are shown in the table below.

[0103] As can be seen from the comparison of Examples 1-4 and Comparative Example 3, when matching cladding doping is achieved by depositing the first group of doping ions (sodium ions and potassium ions) in quartz glass and core doping is achieved by using the second group of doping ions (aluminum ions and titanium ions) in quartz glass, it is beneficial to enhance the Rayleigh scattering signal of acoustic fiber.

[0104] As can be seen from the comparison of Example 4 and Comparative Example 4, using the first group of dopant ions (sodium ions and potassium ions) to deposit in quartz glass to achieve matched cladding doping can enhance the Rayleigh scattering signal of acoustic fiber.

[0105] As can be seen from the comparison of Examples 1-2 and Comparative Examples 2, 1 and 5, using the second group of doping ions (aluminum ions and titanium ions) to achieve fiber core doping in quartz glass is beneficial to enhancing the Rayleigh scattering signal of acoustic fiber.

[0106] As can be seen from the comparison of Example 4 and Comparative Examples 3-5, using either the first group of doped ions or the second group of doped ions alone is beneficial for enhancing the Rayleigh scattering signal of acoustic fiber. Using the second group of doped ions alone is more effective than using the first group of doped ions alone. Compared with using either the first group of doped ions or the second group of doped ions alone, using both groups of doped ions simultaneously is more beneficial for enhancing the Rayleigh scattering signal of acoustic fiber.

[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for fabricating a strong Rayleigh scattering acoustic fiber, characterized in that: Includes the following steps: S1. Preparation: After rinsing the surface of the first quartz base tube with high-pressure ultrapure water, install the first quartz base tube on a precision rotary lathe and perform gas path calibration. S2. Matching cladding doping: The first set of doped ion precursors, matching cladding precursors and carrier gas oxygen are introduced into the first quartz-based glass tube, and the matching cladding is deposited using chemical vapor deposition. S3, Core doping: The second set of doped ion precursors, the core precursors and the carrier gas oxygen are introduced into the first quartz-based glass tube, and the fiber core is deposited by chemical vapor deposition. S4. Collapse: The deposited first quartz base tube is melted and collapsed at high temperature into a solid optical fiber preform core. S5. Sleeve: The optical fiber preform is formed by cladding a second quartz tube on the outside of the optical fiber preform core rod using the sleeve method, followed by high-temperature melting and shrinking. S6. Drawing: The optical fiber preform is drawn to form a strong Rayleigh scattering acoustic fiber. The diffusion coefficient of the first group of doped ions is much greater than that of the second group of doped ions; The first group of doped ions includes sodium ions and potassium ions, and the second group of doped ions includes aluminum ions and titanium ions; The average concentration of sodium ions is 0.2~10 ppm, and the average concentration of potassium ions is 0.2~10 ppm; The average concentration of aluminum ions is 10,000 to 20,000 ppm, and the average concentration of titanium ions is 0.2 to 100 ppm; Both the first and second quartz tubes are high-purity silica-based glass doped with fluorine, with an atomic concentration of 5000~7000 ppm for fluorine and an atomic concentration of no more than 10 ppm for other impurities in the high-purity silica-based glass.

2. The method for fabricating a strong Rayleigh scattering acoustic fiber as described in claim 1, characterized in that: Step S2, the first group of doped ion precursors is a gaseous mixture of potassium chloride and sodium chloride, and the matching cladding precursor is a gaseous mixture of silicon chloride and sulfur hexafluoride.

3. The method for fabricating a strong Rayleigh scattering acoustic fiber as described in claim 1, characterized in that: Step S3, the second group of doped ion precursors is a mixture of aluminum chloride gas and titanium chloride gas, and the core layer precursor is silicon chloride gas.

4. The method for fabricating a strong Rayleigh scattering acoustic fiber as described in claim 1, characterized in that: In steps S2 and S3, during the deposition process, an oxyhydrogen flame torch is used to heat the first quartz substrate from the outside. The temperature of the oxyhydrogen flame is 1800~2000℃, and the first quartz substrate rotates at 50~100 rpm.

5. The method for fabricating a strong Rayleigh scattering acoustic fiber as described in claim 1, characterized in that: In steps S4 and S5, the high-temperature melting and shrinking is achieved by heating with an oxyhydrogen flame torch, and the temperature of the oxyhydrogen flame is 1800~2300℃.

6. A strong Rayleigh scattering acoustic fiber, comprising a cladding, a matching cladding, and a core, characterized in that: The strong Rayleigh scattering acoustic fiber is prepared by the preparation method according to any one of claims 1-5, wherein the diameter of the matching cladding is 2.95 to 3.05 times the mode field diameter.

Citation Information

Patent Citations

  • Optical fiber preform

    CN109250898A